DEVELOPMENT AND PROSPECTS OF INCLUSIVE EDUCATION IN UZBEKISTAN (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The main goal of reforms in the educational system is to ensure equal opportunities for all segments of society and develop the personal potential of each person. From this point of view, inclusive education plays an important role in deciding the principles of social justice and humanism by involving children with disabilities and special needs in the general education system, creating opportunities for them to receive quality education. The quality and effectiveness of the educational system is closely related to the level of socio-economic development of each state. In the context of today's globalization, the issue of creating equal opportunities for all children, guaranteeing the right to education, regardless of their individual characteristics, is becoming relevant. From this point of view, inclusive education is recognized as one of the most important areas of modern pedagogy and educational policy.